Parametric quantile regression models for continuous proportions data : an evaluation of mean versus median modeling beyond beta - Burger, Divan A. (University of Pretoria, 2025)
Mini Dissertation (MSc (Advanced Data Analytics))--University of Pretoria, 2025.